Pengaruh Ukuran Perusahaan, Profitabilitas, dan Net Profit Margin Terhadap Islamic Social Reporting pada Bank Umum Syariah di Indonesia Periode 2017-2021 - Suhailatun Nafisah; Sri Ramadhani (Jurnal Ilmiah Ekonomi Islam, 2023)
This study aims to determine company size, profitability, and net profit margin on Islamic Social reporting (ISR) in Islamic Commercial Bank for the 2017 – 2021. This research uses a quantitative approach. The type of data used is secondary data, namely data, obtained from the annual finansial report (annual report) which is published on the official website of each bank for the period 2017 – 2021. The data analysis method used is multiple linear regression analysis. The results of this study indicate that partially the variabel company size and profitability have a significant effect on Islamic Social Reporting with a significant value of 0,44 < 0,05 and 0,039 < 0,05 while the net profit margin has No. effect on Islamic Social Reporting with a significant value of 0,117 > 0,05. Simultaneously shows that the variable size, profitability, and net profit margin together influence Islamic Social Reporting (ISR) 0,043 < 0,05 and the cowfficient of termination is 52,5 % the rest is explained by causes other than research.